PUSAT PEMBINAAN ANAK JALANAN KOTA BANJARMASIN - Larasati, Ajeng; Sarbini, Gusti Novi (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
Homeless children are unique and creative individuals. Most of the time these homeless children are based in the city center, however, they are often marginalized from the limelight. The homeless children need to be given the opportunity and the choice to improve their potential. The street corners of Banjarmasin are not the ideal home for these children. The Youth Development Center is the place to develop the potential of homeless children through creative fields with a sense of home in the design. It will be the hub for these children to express themselves through their creations and receive the opportunity to learn more without the space restriction. The Youth Development Center can also be a place for society to appreciate the homeless children’s potential. The design strategy uses the Third Place method as a space for interaction and solution of problems using the concept of Flexible Architecture so that space is defined not only by its function but by the potential of the space itself.